SOCIODEMOGRAPHIC AND CLINICAL FACTORS ASSOCIATED WITH LOW AND HIGH GRADE SQUAMOUS INTRAEPITHELIAL LESIONS IN PATIENTS CARED FOR AT THE CARLOS LANFRANCO LA HOZ HOSPITAL DURING THE YEAR 2022 - Dediós Solís, Harold Jhair (2024)
ABSTRACTThe study aimed to determine the association between sociodemographic and clinical factors with the diagnosis of low-grade and high-grade squamous intraepithelial lesions (LIEBG and LIEAG) in patients at the Carlos LanfrancoLa Hoz Hospital in 2022. Materials and Methods. An observational cross-sectional study was conducted with a sampleof 200 patients selected through non-probabilistic sampling. Data were collected from medical records and analyzed using the Chi-Square test. Results. A rate of 14.5% abnormal cytologies was found. Significant associations included age(χ²=45.02, p<0,001), marital status (χ²=18.78,p<0,001), early initiation of sexual activity (χ²=10.51, p=0.010), number ofsexual partners (χ²=10.3, p=0.010), and contraceptive use (χ²=12.83, p=0.004). No significant associations were foundwith educational level (p=0.050), tobacco use (p=0.020), and HPV vaccination (p=0.050).Conclusion The findings suggestthe importance of a personalized approach in cervical cancer prevention, considering the significant risk factors identified.Key words: Risk factors, squamous intraepithelial lesion, Papanicolaou. (Source: MeSH-NLM).